2020
DOI: 10.1016/j.jad.2019.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of assessments of depression (PHQ-9) and anxiety (GAD-7) across sex, strata and linguistic backgrounds in a European-wide sample of patients after Traumatic Brain Injury

Abstract: Measurement invariance of assessments of depression (PHQ-9) and anxiety (GAD-7) across sex, strata and linguistic backgrounds in a Europeanwide sample of patients after Traumatic Brain Injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 43 publications
4
58
0
Order By: Relevance
“…Furthermore, we have not investigated the association between depression and other physical, social, and clinical functioning of the TBI patients given the characteristics of our sample. Teymoori et al [45] found that the functional recovery is a much more important predictor of depression and anxiety severity than the baseline TBI severity, such that individuals with severe and moderate disability six months after the TBI had higher depression and anxiety symptoms in comparison to individuals who had a good recovery after the TBI. Noteworthy, TBI severity was not related to depression and anxiety after controlling for functional recovery measure [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have not investigated the association between depression and other physical, social, and clinical functioning of the TBI patients given the characteristics of our sample. Teymoori et al [45] found that the functional recovery is a much more important predictor of depression and anxiety severity than the baseline TBI severity, such that individuals with severe and moderate disability six months after the TBI had higher depression and anxiety symptoms in comparison to individuals who had a good recovery after the TBI. Noteworthy, TBI severity was not related to depression and anxiety after controlling for functional recovery measure [45].…”
Section: Discussionmentioning
confidence: 99%
“…We used the translated versions of the PHQ-9 and GAD-7 questionnaires that were available in the relevant languages (see https://www.phqscreeners.com/select-screener/36) and were shown to be valid and invariant across different sex, patient strata, and languages [45]. Following a procedure recommended by Acquadro, Conway, Giroudet, and Mear [46], GOSE and PCL-5 were translated, back-translated, panel-reviewed, and finally underwent a cognitive debriefing with several patients and healthy participants.…”
Section: Instrumentsmentioning
confidence: 99%
“…However, it was worth noting that their prevalence of mental issues was lowered than that of health workers in the local hospitals during the COVID-19 outbreak. Huang and colleagues' study revealed that the prevalence of depression and anxiety of health workers in the local hospitals was as high as 50.7% and 44.7%, respectively [9]. Meanwhile, our study shows that the 22.7% of military health workers with depression symptoms had comorbid anxiety and somatization, which was lower than that of primary care clinic patients in the United States [5].…”
Section: Discussionmentioning
confidence: 49%
“…The GAD-7 is a brief self-report scale and efficient tool for screening General Anxiety Disorder (GAD) with seven items rated on a 4-point Likert-scale ranging from 0 (not at all) to 3 (nearly every day) (8,9). The total score represents minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21) anxiety symptoms, respectively. In the present study, the Cronbach's ɑ was 0.92, test-retest reliability was also good (intraclass correlation = 0.83) (8).…”
Section: Instrument Anxietymentioning
confidence: 99%
“…The Patient Health Questionnaire 9 (PHQ-9) is a widely used instrument to measure the depression of the subjects, which includes nine questions rated on a four point scale ranging from 0 (not at all) to 3 (nearly every day). A total score ranges from 0 to 27 is categorized into minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20-27)(10). In the PHQ Primary Care Study,the Cronbach's α was 0.89 test-retest reliability was excellent(intraclass correlation = 0.84) (11).…”
Section: Depressionmentioning
confidence: 99%